Diffracted Landscapes of Attention: Jon McGregor’s Reservoir 13 - Jean-Michel Ganteau (Études Britanniques Contemporaines, 2018)
With Reservoir 13 (2017), Jon McGregor tills the field of attentiveness to the ordinary and continues his onslaught on character. He also goes about blowing away the conventions of pastoral and landscape writing, to the accompaniment of the mines blasting off whole faces of the quarry hanging somewhere in the hills above the unnamed village around which the whole of the action revolves. The novel uses the pretext of an incipient detective plot as a red herring, the better to concentrate on the natural rhythms and recurrent human and animal activities whose routine is regularly punctured by the vivid memory of a 13-year-old girl’s disappearance in the hills. In this article I show that the novel’s evocation of place rejects the conventions of distancing and objectification the better to provide an ethical and phenomenological perspective (Omhovère). By opting for the minuteness of perception and addressing the ordinary and the everyday, it eschews any attempt at totalisation inherent in more traditional landscapes by figuring out a field of possibilities that favour shifts and changes (Berberich, Campbell and Hudson). The non human, object components of the landscape are seen to be both affected and affecting, creating a relational space that is both the product and condition of an expressive landscape stridently animated by the vibrancy (Bennett) of water, stone, flowers and trees. The paratactic logic and the refusal of hierarchy and causality demand an attentiveness to singularities that promotes the slowness of attention and reminds the reader that in attentiveness begins responsibility (Foley Sherman).